The Role of Child Criminal Justice Unit (PPA) In Handling Cases of Children Feeling with The Law at Polrestabes Semarang - Lalu Hedwin Hanggara; Faisal Santiago (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
The position of children in a country is the continuation of the nation's struggle. Therefore, their existence must be maintained properly from things that can damage the child's mentality. One of them is a child whose actions against the law. Many children think that this act is a normal thing, but, legally speaking, the act committed by the child is included in the category of a criminal act, one of which is beatings. This study aims to find out and analyze the implementation of diversion against children who are perpetrators of the crime of beatings in the concept of justice at the Semarang Police and the effectiveness of applying diversion to children who are involved in the crime of beatings at the Semarang Police. The approach method in this research is normative juridical. The results of the study show that the implementation of diversion against children who commit the crime of beatings in the concept of justice at Polrestabes Semarang following the provisions of Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. The diversion process involves all, namely the victim's family, the perpetrator's family, and the Bapas, namely through deliberations involving children and their parents/guardians, victims and/or their parents/guardians, and community counsellors, based on a restorative justice approach. The application of diversion to the child perpetrators of the Semarang Police crime is very effective in resolving criminal acts of beatings with child perpetrators. The procedure for settlement of cases becomes simpler, cheaper, and saves time through diversion. The implementation of diversion is also able to reduce the build-up of cases being handled at the Semarang Police, reducing the cost burden.